Microbial Control of the Potato Tuber Moth Phthorimaea operculella (Lepidoptera: Gelechiidae) - LACEY, LAWRENCE A.; KROSCHEL, JÜRGEN; ARTHURS, STEVEN P.; DE LA ROSA, FRANCISCO (Revista Colombiana de Entomología, 2010)
The natural occurrence of specific pathogens and biopesticides applied in an inundative fashion can contribute significantly to control of the potato tuber moth, Phthorimaea operculella. Most of the research conducted and practices used for control of P. operculella use one species of granulovirus and the bacterium Bacillus thuringiensis (Bt). The P. operculella granulovirus (PhopGV) has the potential to play a significant role in the integrated management of the pest in stored tubers as well as in field crops. At the same time, Bt has been used successfully against P. operculella infestations in the field and in stored tubers. PhopGV and Bt are safe for application personnel and for the food products; in addition, they do not affect beneficial insects and other nontarget organisms. Other natural insecticides are the biofumigant fungus Muscodor albus, botanicals, sex pheromones and physical measures for P. operculella control in stored tubers. The implementation of biopesticides will ultimately depend on an increased awareness of their attributes by growers and the public, who will be the main drivers for their use and commercialization.